Genetic variations among Indonesian native cattle breeds based on polymorphisms analysis in the growth hormone loci and mitochondrial DNA - SUTARNO SUTARNO (Biodiversitas Journal of Biological Diversity, 2010)
Sutarno (2010). Genetic variations among Indonesian native cattle breeds based on polymorphisms analysis in the growth hormone loci and mitochondrial DNA. Biodiversitas 11: 1-5. Genetic variation within breeds is important and its study has become a subject of interest in livestock species, as it has many applications in animal breeding and genetics, such as the identification of animals and parentage testing, gene mapping and identifying markers for performance traits. Two loci of bovine growth hormone genes, and two regions of mitochondrial DNA, D-loop and ND-5 were characterized using polymerase chain reaction – restriction fragment length polymorphism (CR-RFLP) involving 120 Indonesian native cattle of Bali, Madura, PO and West Sumatra breeds. The results indicated that sequence variations were detected both in the growth hormone loci and mitochondrial DNA.